Evaluation of the Implementation of the Green Building Concept in Mid-Rise Buildings - Meisy Ariani; M. Heri Zulfiar (DIMENSI (Journal of Architecture and Built Environment), 2025)
This research looks into how Green Building principles are implemented to two medium-rise educational buildings placed in Yogyakarta: the Djarnawi Hadikusuma Building (E8) at Universitas Muhammadiyah Yogyakarta and the Integrated Forest Farming Learning Center (IFFLC) at Universitas Gadjah Mada. Referring to the Greenship Existing Building guidelines version 1.1, the data collection process is carried out by using on the spot surveys, measuring indoor air quality (IAQ), and reviewing allied project documents, then assessed with SPSS and Monte Carlo simulations. The results of the study illustrate that the cumulative performance of both buildings is in the very good category (Index Score 4.58; Risk Index 0.42). The Indoor Health and Comfort (IHC) quality is the strongest performing category, while Water Conservation (WAC) and Material Resources and Cycle (MRC) still need further improvement. The indoor air quality analysis also pointed out that the UGM building needs enhancements in its ventilation system and VOC control, while UMY needs to sustain the regularity of its already well-running operational management. The risk analysis corroborates the significance of cohesive management to decrease potential inadequacies while making sure the comfort for people. The findings also deliver particular guidance on steps to improve sustainability performance in mid-rise educational buildings.